Supporting patients with female genital mutilation in primary care: a qualitative study exploring the perspectives of GPs' working in England - Dixon, S; Hinton, L; Ziebland, S (Royal College of General Practitioners, 2020)
Background: Female genital mutilation (FGM) includes all procedures that intentionally harm or alter female genitalia for non-medical reasons. In 2015, reporting duties were introduced, applicable to GPs working in England including a mandatory reporting duty and FGM Enhanced Dataset. Our patient and public involvement work identified the exploration of potential impacts of these duties as a research priority.